Honda‘s Market Presence in China: A Study of Brand Loyalty and Consumer Decisions - Zhang, Yan (Transactions on Economics, Business and Management Research, 2024)
In recent years, the Chinese automobile market has evolved into a mature stage, where product demand remains relatively stable. Under such circumstance, fostering and maintaining brand loyalty has emerged as a critical strategic priority for major automakers. The rationale behind this is clear: retaining loyal customers is a key driver of sustained profits and market share. Drawing insights from Honda's lackluster sales performance in China since 2020 and buttressed by comprehensive literature review, this article delves into the intricate factors that shape brand loyalty and their subsequent impact on consumer behavior. Notably, brand image, technological innovation, and service excellence serve as the cornerstone elements. Furthermore, this article outlines various strategies and initiatives that car manufacturers can adopt to enhance brand loyalty, thereby strengthening their foothold in the competitive Chinese automotive landscape. Through rigorous analysis and literature review, this article explores the pivotal role of brand image, technological advancements and service excellence in fostering brand loyalty and offers strategies to enhance it.